The Curse of Totalitarianism and the Challenge of Critical Pedagogy - Giroux, Henry A. (Chowanna, 2020)
Expanding critical pedagogy as a mode of public pedagogy suggests being attentive to and addressing modes of knowledge and social practices in a variety of sites that not only encourage critical thinking, thoughtfulness and meaningful dialogue, but also offer opportunities to mobilize instances of moral outrage, social responsibility and collective action. Such mobilization opposes glaring material inequities and the growing cynical belief that today’s culture of investment and finance makes it impossible to address many of the major social problems facing the United States, Canada, Latin America and the larger world. Most importantly, such work points to the link between civic education, critical pedagogy and modes of oppositional political agency that are pivotal to creating a politics that promotes democratic values, relations, autonomy and social change.